2017
DOI: 10.4103/1735-1995.200275
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of rituximab in neuromyelitis optica: Review of evidence

Abstract: Neuromyelitis optica (NMO) is an autoimmune inflammatory disease of the central nervous system with preferential involvement in the optic nerve and spinal cord with a widespread spectrum of clinical features; multiple therapeutic agents have been used with different results. Recent evidence points to B-cell-mediated humoral immunity in the pathogenesis of NMO. Rituximab targets the CD20 antigen on B-cells. Treatment leads to profound B-cell depletion, principally over an antibody-dependent cell cytotoxicity me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(9 citation statements)
references
References 35 publications
(45 reference statements)
1
8
0
Order By: Relevance
“…In addition, when we performed the Kaplan-Meier analysis, we found that low-dose RTX significantly delayed the time to relapse in the NMOSD patients in both the overall series and the subgroup that previously received NSISs. Notably, the efficacy observed in our case group was similar to that in other studies using standard-dose therapy ( 18 , 19 , 23 , 24 ), although the methods used in each study were heterogeneous.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, when we performed the Kaplan-Meier analysis, we found that low-dose RTX significantly delayed the time to relapse in the NMOSD patients in both the overall series and the subgroup that previously received NSISs. Notably, the efficacy observed in our case group was similar to that in other studies using standard-dose therapy ( 18 , 19 , 23 , 24 ), although the methods used in each study were heterogeneous.…”
Section: Discussionsupporting
confidence: 83%
“…There is a significant proportion of patients with MS and NMOSDs who positively respond to anti-CD20 drugs such as RTX. 11 , 21 Thus, it is vital to consider the side effects of these drugs from a wider temporal perspective, given the long-term treatment regimens used in the management of these diseases. RTX has been used “off label” for more than a decade in NMOSDs.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 After more than 2 decades of use, RTX is widely prescribed not just in the treatment of non-Hodgkin lymphomas, 3 in which it was first approved, but for a variety of autoimmune diseases wherein depletion of circulating CD20 + B cells is the common therapeutic goal. 4 9 It is also an effective, yet off-label treatment for neuromyelitis optica spectrum disorders (NMOSDs), 10 , 11 a group of inflammatory immune-mediated demyelinating disorders of the CNS. 12 , 13 Ample evidence exists for major side effects including hypogammaglobulinemia (hypo-Ig) after a prolonged treatment with RTX in patients with rheumatologic 14 16 diseases (table e-1, links.lww.com/NXI/A70 ).…”
mentioning
confidence: 99%
“…Three mAbs, rituximab, ocrelizumab, and ofatumumab, are currently in clinical use for MS. Rituximab, a chimeric mouse-human monoclonal antibody, was approved in 1997 for B cell lymphoma and indeed was one of the first mAbs ever developed for clinical use. 71 Rituximab was approved for rheumatoid arthritis (RA) in 2006, and has now been used in more than 184,000 patients with RA, 72 as well as off-label use in IgG4 disease, 73 pemphigus, 74 ANCA vasculitis, 75 neuromyelitis optica, 76 and myasthenia gravis, 77 in addition to widespread use in MS. Rituximab works primarily through complement-dependent cytotoxicity (CDC) of B cells, but also has significant antibody-dependent cellular cytotoxicity (ADCC) activity.…”
Section: Anti-cd20 Therapymentioning
confidence: 99%